Strategies toward catalytic biopolymers: Incorporation of tungsten in alginate aerogels. (1st November 2018) - Paraskevopoulou, Patrina; Gurikov, Pavel; Raptopoulos, Grigorios; Chriti, Despoina; Papastergiou, Maria; Kypritidou, Zacharenia; Skounakis, Vassilis; Argyraki, Ariadne
Graphical abstract: Tungsten-doped alginate aerogels were obtained by impregnating alginate alcogels with an ethanolic solution of [W2 ( μ -OEt)2 (OEt)2 (EtOH)2 Cl4 ] (W = W 8+ ). They contained 10% w/w tungsten, and had low bulk densities (<0.1 g/cc), high porosities (96% v/v) and high BET surface areas (380 m 2 /g). Pyrolysis at 800 °C under O2 yielded CaWO4 and Ca3 WO6 (10:90 w/w). Abstract: We report the synthesis of W-doped biopolymer aerogels with potential applications to catalysis. The biopolymers were based on alginate, a cost-efficient natural material, and were prepared in environmentally friendly water/ethanol solutions. Gelation of alginate was induced by crosslinking with Ca 2+ . The resulting wet-gels were impregnated with an ethanolic solution of the ditungsten complex [W2 ( μ -OEt)2 (OEt)2 (EtOH)2 Cl4 ] (W = W 8+ ) and were dried with supercritical fluid (SCF) CO2 to yield W-doped alginate aerogels containing 10% w/w tungsten. Dry materials were characterized with FTIR, SEM/EDS, TGA, N2 porosimetry and He pycnometry. The bulk densities were low (<0.1 g cm −3 ), porosities were high (96% v/v), as well as the BET surface areas (380 m 2 /g). Pyrolysis of those aerogels at 800 °C under Ar yielded carbon along with a mixture of calcium tungstates, i.e., CaWO4 and Ca3 WO6 (weight ratio: 70:30), while pyrolysis under O2 yielded the same tungstates, but with a different weight ratio (10:90). This can be a new process for Ca3 WO6, which, due to its ordered double perovskite structure, is ideal for doping with metal ions, at relatively low temperature (800 °C versus >1000 °C in the literature).